Aplikasi Mobile Android Layanan Bengkel Sepeda Mas Ung Home Bike Workshop - Muriyatmoko, Dihin; Sempana Hidayat, Lingga; Harmini, Triana (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2024)
A bicycle workshop is an important place for bicycle users for maintenance and repairs. However, workshops often face challenges in providing effective and efficient services, such as managing customer data, handling repairs, bookkeeping, and product sales. This research focuses on developing an Android-based information system at Mas Ung Home Bike Workshop, a bicycle workshop in Cikarang, West Java. Based on interviews with the workshop owner, several issues were identified with the current application, such as the complexity of operating the previous application, the lack of documentation features in the form of photos and videos before and after repairs, and the need for invoices containing the workshop's bank account number. This research uses the waterfall software development model, which includes requirement analysis, system and software design, implementation and unit testing, integration and system testing, as well as operation and maintenance. The result of this research is an Android-based bicycle workshop service application with features such as transaction recording, repair reports including photos and videos, transaction reports, and invoice printing with the workshop owner's account name and number. With an integrated information system, it is expected to help improve the service at Mas Ung bicycle workshop.